Ecologia populacional e reprodutiva de Pygoscelis antarcticus e Eudyptes chrysolophus em Stinker Point - Ilha Elefante - Werle, Gabriela Bandasz (Universidade do Vale do Rio dos Sinos, 2014)
Elephant Island differentiated by being the northernmost island of the South Shetlands archipelago and by having different climatic characteristics (O'Brien, 1974). Present ice-free areas, serve as a breeding site for various bird species. And regarding the avifauna present at the site, there are 14 breeding species: Pygoscelis papua, Pygoscelis adeliae, Pygoscelis antarcticus, Eudyptes chrysolophus, Aptenodytes patagonicus, Macronectes giganteus, Daption capense, Oceanites oceanicus, Fregetactata albacta, Chitta cana, Phalacan 1994). The species Pygoscelis antarcticus (Figure 1) or Antarctic penguin, as it is popularly known, belongs to the order Sphenisciformes and the family Spheniscidae, has a medium height (71-76 cm), with black coloration on the posterior part of the body and white on the anterior part. , near the chin has a black line, characteristic of this species and has a black beak (Willians, 1995). This penguin species has a circumpolar distribution, being found in Antarctica, the South Sandwich Islands, Orkneys Islands, South Shetlands, South Georgia, Bouvet and Balleny (BirdLife International 2012). However, in terms of breeding areas, this species breeds almost exclusively in the islands of Scotland and the Antarctic Peninsula south of the 65C parallel (Stonehouse, 1975; Kooyman, 2002). , Euphasia superba, but also feeds on fish, cephalopods and other crustaceans.
Keywords: Ecologia populacional e reprodutiva; Pinguins; Mapeamento; Número de pares reprodutivos; Filhotes em creche; Sucesso reprodutivo; Population and reproductive ecology; Penguins; Mapping; Number of breeding pairs; Puppies at the daycare; Reproductive success; ACCNPQ::Ciências Biológicas::Biologia Geral